Road Infrastructure Condition Analysis in Terms of Road Quality in Bengkulu City - Pujiyono, Sugeng; Nugroho, Laksono Djoko; Muhammadun, Haris (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
The purpose of this research is to explain the analysis of road infrastructure conditions, in terms of road quality in Bengkulu City. The research method uses descriptive with qualitative approach, Research Subjects, are people and government institutions, key informants are all people or officials related to road infrastructure policy makers, traffic density and road quality, such as traffic police, transportation department, PUPR department, BPS Bengkulu City.  The results of the study explain that the level of traffic density in Bengkulu City is categorized as moderate (26 vehicles / km), the population density of Bengkulu City is known to be categorized as moderate, in accordance with the demographic situation (population density) calculated per square kilometer (Km²) in 2024 is 2,600 people / km², the quality of roads in Bengkulu City is well qualified, although there are several road sections that experience cracking. The occurrence of road cracks is found on 15 (fifteen) road sections amounting to 2.340%. The data shows that cracking does not significantly reduce road quality as there are still 97.660% of roads with good quality.